Orientation stabilized rapid melting growth of thin (100) ge-on-insulator structures and their implementation in homoepitaxial growth - Anisuzzaman, Mohammad (2013)
Integration of Ge on the Si platforms is essential for the development of next generation large-scale integrated circuits. The Ge-on-insulator (GOI) structure is suited for the realization of high-mobility transistors channels and as epitaxial templates for optoelectronic and spintronic materials. In this work, the fabrication of thin (~50 nm) (100) GOI by the rapid melting growth process has been investigated. Growth with unstable crystal orientation has been observed in wide (=1 µm) GOI strips. However, orientation stabilized growth was achieved in narrow strips (~0.5 µm). Further stabilization of growth orientation was observed in mesh patterned growth with GOI width of 1 µm. Epitaxial growth of Ge was performed on the above structures and the formation of uniform epitaxial layer was demonstrated.